2013
DOI: 10.5812/hepatmon.7862
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Telbivudine Compared to Entecavir Among HBeAg+ Chronic Hepatitis B Patients: a Meta-Analysis Study

Abstract: BackgroundHepatitis B virus (HBV) infection is a serious global health problem that is associated with huge social and economic costs. Early antiviral drugs, such as interferon-α2b, peginterferon-α2a, lamivudine, and adefovir, all have their limitations (such as low responses or safety concerns) in clinical application. Telbivudine and entecavir are two of the latest nucleotide drugs and both have been shown to have potent viral suppression. However, in patients with hepatitis B e antigen (HBeAg)-positive chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For treatment of HBeAg ϩ mothers during late pregnancy, telbivudine was well tolerated, with no severe side effects in telbivudine-treated mothers or their infants (112). Although entecavir is superior to telbivudine in safety, both telbivudine and entecavir offer similar drug efficacies in terms of the cumulative rates of undetectable HBV DNA and alanine aminotransferase levels (113). For first-line therapy of HBV infections, the use of entecavir is strongly recommended, especially in children aged 2 to 12 years (114).…”
Section: Nucleoside Analoguesmentioning
confidence: 99%
“…For treatment of HBeAg ϩ mothers during late pregnancy, telbivudine was well tolerated, with no severe side effects in telbivudine-treated mothers or their infants (112). Although entecavir is superior to telbivudine in safety, both telbivudine and entecavir offer similar drug efficacies in terms of the cumulative rates of undetectable HBV DNA and alanine aminotransferase levels (113). For first-line therapy of HBV infections, the use of entecavir is strongly recommended, especially in children aged 2 to 12 years (114).…”
Section: Nucleoside Analoguesmentioning
confidence: 99%
“…A systemic review also confirmed these findings [31]. Compared with ETV, which bears a high genetic barrier to drug resistance, several meta-analyses indicated that shortterm LdT treatment had a more favorable serologic response than ETV, but a higher rate of genotypic resistance [32][33][34]. Nevertheless, several advantages of LdT such as its safety for pregnant females [35] and improvement of renal function in patients with baseline mild renal dysfunction [36] should not be overlooked.…”
Section: Dynamics Of Qhbsag During Ldt Treatmentmentioning
confidence: 60%
“…Telbivudine, a potent antiviral, is an orally administered synthetic thymidine nucleoside analog with specific activity against HBV . The general efficacy of telbivudine (ability to reduce HBV DNA and ALT levels and stimulate HBeAg seroconversion) has been discussed extensively in literature reviews and meta‐analyses . A more recent network meta‐analysis demonstrated the superiority of telbivudine over adefovir, entecavir, and lamivudine in HBeAg seroconversion or HBeAg loss .…”
Section: Treatment Response To Telbivudine In Patients With Chronic Hmentioning
confidence: 99%
“…18,27 The general efficacy of telbivudine (ability to reduce HBV DNA and ALT levels and stimulate HBeAg seroconversion) has been discussed extensively in literature reviews and meta-analyses. [28][29][30] A more recent network meta-analysis demonstrated the superiority of telbivudine over adefovir, entecavir, and lamivudine in HBeAg seroconversion or HBeAg loss. 31 Although the short-term efficacy of telbivudine with regard to the rate of undetectable HBV DNA level appears to be comparable with entecavir, the results showed improved suppression of HBV DNA with long-term telbivudine treatment in comparison with adefovir and lamivudine.…”
Section: Treatment Response To Telbivudine In Patients With Chronic Hmentioning
confidence: 99%